NATO’S PROSPECTS IN THE LIGHT OF THE UKRAINE WAR (Annual of the Faculty of Philosophy in Skopje, 2022)
The war on Ukraine, which began on 24 February 2022 with the invasion of the armed forces of the Russian Federation, is an event with a potential to cause tectonic changes in the current political, security and economic international order, including the possibility of a nuclear conflict. As it is the case with the other international and regional organizations, NATO too is enforced to reconsider its position in the multipolar world. The research problem of this paper is delimiting the reality from the myth of NATO that has rested for decades. It focuses on the search for the Alliance’s real power in a multipolar international system, as well as seeking answers about the future of the European security order (especially through the prism of NATO-EU relations). The key hypothesis is that the course of events (in Ukraine but also the definite rise of multipolar international system) has been predictable. The reasons for the war were deeply embedded in the foundations of the hybrid international system. The preliminary conclusion is that NATO (albeit seemingly strengthened and expanded) will likely face with its irrelevance in a multipolar order. The thesis of a “global NATO” is just a veil that covers the restricted NATO mission primarily as an instrument of the US policy in Europe. Due to the Ukraine, EU (but also OSCE) is likely to see the shattered dreams of its own security system. It means it will be economically, politically and militarily completely dependent on Washington. NATO enlargement is reaching its peak, along with its primarily European reach. Globally, the United States will rely on its own forces and on alliance of the willing, now referred to as the “Collective West.”
Keywords: NATO; RUSSIA; UKRAINE; WAR; ENLARGEMENT; MULTIPOLAR ORDER